2013
DOI: 10.1136/jmedgenet-2013-101937
|View full text |Cite
|
Sign up to set email alerts
|

Different mutations inPDE4Dassociated with developmental disorders with mirror phenotypes

Abstract: Our findings indicate that haploinsufficiency of PDE4D results in a novel intellectual disability syndrome, the 5q12.1-haploinsufficiency syndrome, with several opposing features compared with acrodysostosis that is caused by dominant negative mutations. In addition, our results expand the spectrum of PDE4D mutations underlying acrodysostosis and indicate that, in contrast to previous reports, patients with PDE4D mutations may have significant hormone resistance with consequent endocrine abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 28 publications
2
75
0
1
Order By: Relevance
“…(15,18,pts P1/P2) Interestingly, structural variants of chromosome 5q12.1 determining haploinsufficiency of PDE4D resulted in a novel intellectual disability syndrome, but several opposing features compared with acrodysostosis (characteristic faces with prominent nasal bridge and maxillary hyperplasia, low body mass index [BMI], and long extremities and fingers). (17) The review of published mutations associated to ACRDYS (summarized in Tables 2 and 3) demonstrated that PRKAR1A/ PDE4D genetic variants may affect different functional domains and are mainly private mutations. Only few variants recurred in more than one unrelated case, but because ACRDYS-associated genes have been recently discovered, the number of recurrent mutations is likely to increase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(15,18,pts P1/P2) Interestingly, structural variants of chromosome 5q12.1 determining haploinsufficiency of PDE4D resulted in a novel intellectual disability syndrome, but several opposing features compared with acrodysostosis (characteristic faces with prominent nasal bridge and maxillary hyperplasia, low body mass index [BMI], and long extremities and fingers). (17) The review of published mutations associated to ACRDYS (summarized in Tables 2 and 3) demonstrated that PRKAR1A/ PDE4D genetic variants may affect different functional domains and are mainly private mutations. Only few variants recurred in more than one unrelated case, but because ACRDYS-associated genes have been recently discovered, the number of recurrent mutations is likely to increase.…”
Section: Discussionmentioning
confidence: 99%
“…1). (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Considering the distribution of the mutations, exon 11 is the most affected site (52.9%), followed by exon 9 (23.5%), exon 7 (17.6%), and exon 8 (5.9%). No mutations were observed in other exons, acceptor-donor splice sites, and introns.…”
Section: Prkar1a Mutation Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Acrodysostosis is uncommon; the prevalence of the disease is unknown, and clinical, biochemical and radiological features overlap with those of PHP1A and PPHP 6,[11][12][13][14][15] .…”
mentioning
confidence: 99%